KURUMSAL MARKA ÇERÇEVESİNDE BAŞARILI BİR MARKANIN YARAR VE ETKİLERİ ÖRNEK FİRMA: BİR MARKA EFSANESİ OLAN "VESTEL". - KURTBAŞ, İHSAN (Fırat Üniveristesi, 2007)
In today?s market each and every day new emergant competitors come into marketwith new and improved marketing strategies to turn consumer preferences into their side.Increase in information level and life standards leads to dissatisfaction of consumer and it istoo hard to persuade and influence the consumers. Because consumers are bombed toinformation and message and this leads to the fullness of consumers and reach to the point ofsensation. To get emotional tide with consumer in such a crovded environment of goods,services and brands is to get trademark. Brand is a series of quality which bought byconsumers and got satisfactions to them. With this instance it differs from product. Product isa thing that produce in factory and brand is a thing that is an unique idea or concept take placein consumers? mind. One of the important aspect of branding is positioning of it inframework of differentiation. In this point if you want to build a brand you must focus on tohave a word in mind of consumer. The word that nobody have it. Finally branding gives manygaining to firms, products and services such as differentiation and preference, have a prestigebrand, demand higher prices.In this study, we examine the Zorlu group?s leading brand of Vestel. It?s process ofbranding, pronunciation of process, brand positioning, brand look, and it?s position in theleague of Turkish brand are taken into consideration.Key Words: Brand, Institutional Identity, Advertisement, Consumption, Marketing,Vestel
Influences and benefits of successful brand in the framework of institutional brand case firm: Vestel the legend of a brand
Keywords: Halkla İlişkiler; İletişim Bilimleri; Radyo-Televizyon